Attitudes and beliefs about violence in secondary-school adolescents - Viniegra Cabello, María (Pulso. Revista de educación, 2007)
In the article below you can fi nd recent data about attitudes and believes of youngsters regarding violence, and its evolution along time. There are also opinions regarding two different moments (years 2003 and 2005) which allow to appraise possible changes in the attitudes of a group of youngsters studying the Spanish Secondary Stage. The results allow us to think about the quality and effi ciency of the performance which are being carried out against the fundamentals of violence and intolerance.
Keywords: Gender; Attitudes and Beliefs Around Violence; School Violence